Hell's half acre : cold-blooded - Johnstone, William W. (Johnstone, William W. Hell's half acre, 2015)
"Sheriff Jess Casey and his oddball band of sidekicks have pulled off the impossible, taming Hell's Half Acre, the most lawless town in Texas, infamous for murder, mayhem, prostitution, and every random act of bloodshed imaginable. Now the no-good politicians in Austin have decided it's cheaper to dump hordes of criminals on Jess Carey's town than hanging 'em. In one dreadful week it seems as if the gates of Hell have burst open. Freed outlaws, gunslingers, bandits, rapists, desperados, drifters and miscreants are roaming Hell's Half Acre--and Jess and his deputies are running out of bullets fast. As the fighting rages, some ruthless, powerful men see their chance to kill Sheriff Jess Carey and take the town for their own..."--Back cover.